2018
DOI: 10.1136/bcr-2018-224537
|View full text |Cite
|
Sign up to set email alerts
|

Transient immune-mediated agranulocytosis followingMycoplasma pneumoniaeinfection

Abstract: is a common respiratory pathogen which may cause haematological manifestations including haemolytic anaemia and thrombocytopaenia. Severe neutropaenia is rare with very few cases reported in the literature. An 85-year-old man was transferred to our facility with agranulocytosis in the context of an infective exacerbation of chronic obstructive pulmonary disease with positive serological testing for No alternative infective, autoimmune or lymphoproliferative cause of the neutropaenia was identified. Granulocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Our results showed that Mycoplasma in the lung increased significantly in the COPD model group compared with the control group while decreased significantly after QBPF intervention. Mycoplasma is a notable species traditionally associated with infection [ 80 ], and Mycoplasma pneumonia is a common respiratory pathogen [ 81 ]. Rikenellaceae_RC9_gut_group in the lung decreased significantly in the COPD model group compared with the control group while increased significantly after QBPF intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that Mycoplasma in the lung increased significantly in the COPD model group compared with the control group while decreased significantly after QBPF intervention. Mycoplasma is a notable species traditionally associated with infection [ 80 ], and Mycoplasma pneumonia is a common respiratory pathogen [ 81 ]. Rikenellaceae_RC9_gut_group in the lung decreased significantly in the COPD model group compared with the control group while increased significantly after QBPF intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that Mycoplasma in the lung increased significantly in the COPD model group compared with the control group while decreased significantly after QBPF intervention. Mycoplasma is a notable species traditionally associated with infection [85], and Mycoplasma pneumonia is a common respiratory pathogen [86]. Rikenellaceae_RC9_gut_group in the lung decreased significantly in the COPD model group compared with the control group while increased significantly after QBPF intervention.…”
Section: There Exists Regulation Of Qbpf In Immune Homeostasis and In...mentioning
confidence: 99%
“…In recent years, MMP accounts for 10%-40% of community acquired pneumonia (CAP) in children, especially in Asia [1]. If the host cannot effectively clear the pathogen of mycoplasma pneumoniae, immune response will continuously damage of the respiratory epithelium and cilia [2,3]. In addition, drug resistant MP strains are more and more common.…”
Section: Introductionmentioning
confidence: 99%
“…populationA total of 233 MMP pediatric patients were included in the study, with 121 males and 112 females, aged 4.541(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years. Among them, 84 pediatric patients were diagnosed as SMPP, with the incidence of 36.1% (95% CI 29.9%-42.6%).…”
mentioning
confidence: 99%